2015
DOI: 10.1016/j.jalz.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Combined Alzheimer's disease and cerebrovascular staging explains advanced dementia cognition

Abstract: The combination of scales measuring cerebral vascular and Alzheimer's type pathology allowed a classification of patients that reveals differences between groups in premortem cognitive features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Clinical features are listed in the Table. Procedures for brain tissue extraction, processing, and neuropathological classification had been published before. 28,29 Postmortem brain tissue was obtained from donors through a rapid neuropathological autopsy (mean postmortem interval = 5.5 hours). After brain removal, two symmetric brain halves were obtained through a midsagittal incision and the right hemibrain was flash-frozen by immersion in -60 C isopentane.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical features are listed in the Table. Procedures for brain tissue extraction, processing, and neuropathological classification had been published before. 28,29 Postmortem brain tissue was obtained from donors through a rapid neuropathological autopsy (mean postmortem interval = 5.5 hours). After brain removal, two symmetric brain halves were obtained through a midsagittal incision and the right hemibrain was flash-frozen by immersion in -60 C isopentane.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, epidemiological studies have increasingly demonstrated that traditional vascular risk factors, such as obesity, diabetes and hypertension, have important etiological roles not only in vascular dementia but also in AD [79]. Due to the increased recognition of a significant overlap between these conditions, there is a need to examine vascular dementia and AD beyond a simple dichotomy, but as part of a continuous spectrum of age-related dementia where factors contributing to either vascular dementia or AD are considered together [15]. …”
Section: Vascular Dementia and Alzheimer’s Disease: Age-related Demenmentioning
confidence: 99%
“…These patients can be closely studied within the center's facilities offering valuable information on their disease progress and ways to maximize management. The foundation's research has shown that lower cardiac hemodynamic performance is significantly associated with structural brain damage that parallels diminished executive function and other cognitive brain abnormalities [74]. A large brain bank facility is the source of multiple neuropathological research studies.…”
Section: Preventive Alzheimer's Clinicsmentioning
confidence: 99%